2015
DOI: 10.3389/fpsyg.2015.01835
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Moderate the Effect of Workload Sources on Perceived Workload in Flying Column Police Officers

Abstract: Previous research has suggested that personality traits of the Five Factor Model play a role in worker's response to workload. The aim of this study was to investigate the association of personality traits of first responders with their perceived workload in real-life tasks. A flying column of 269 police officers completed a measure of subjective workload (NASA-Task Load Index) after intervention tasks in a major public event. Officers' scores on a measure of Five Factor Model personality traits were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 75 publications
4
21
0
Order By: Relevance
“…The results confirm hypothesis 2. On the other hand, the results of this study show that there is no significant relationship between personal resources (PsyCap) and job demands (workload), which coincides with previous research [58,59]. Other studies have shown the mediation role of personal resources on the relationship between workload and burnout in specific simples (nurses, policies) [60], which it could be considered to future research.…”
Section: Discussionsupporting
confidence: 85%
“…The results confirm hypothesis 2. On the other hand, the results of this study show that there is no significant relationship between personal resources (PsyCap) and job demands (workload), which coincides with previous research [58,59]. Other studies have shown the mediation role of personal resources on the relationship between workload and burnout in specific simples (nurses, policies) [60], which it could be considered to future research.…”
Section: Discussionsupporting
confidence: 85%
“…Yet in another study, Antoniou et al (2013) in Greece showed that rational coping behaviours and one's personality are a resource which help teachers to overcome work related stressors and burnout and achieve their valued outcomes with the students, while avoidance coping predicted a secondary level of stress and burn out. Similarly, Chiorri et al (2015) study in Turkey indicated that all Type B personality trait except extraversion significantly interacted at least with one workload source.…”
Section: Introductionmentioning
confidence: 86%
“…For example, a recent study has found that the character strength as personality trait can be improved through training of employees to mitigate the negative work related behaviours (Harzer & Ruch, 2015). The work load sources and perceived workload can be moderated by personality traits (Chiorri, Garbarino, Bracco, & Magnavita, 2015). The leadership personality traits (neuroticism and conscientiousness) among mangers or the individuals having leadership role in any working environment can infuse stress among subordinates (Robertson , Healey, Hodgkinson, Flint-Taylor, & Jones, 2014).…”
Section: Occupational Stressmentioning
confidence: 99%